Child with Kawasaki Disease Complicated by A Single Right Coronary Artery. Issue 15 (April 2021) - Nakagawa, Ryota; Ishido, Hirotaka; Iwamoto, Yoichi; Sekine, Mai; Momose, Taichi; Tanikawa, Shoyo; Moriwaki, Koichi; Masutani, Satoshi
A 3-year-old boy was referred to our hospital for management of Kawasaki disease at 5 days of illness. Echocardiographic examination on admission suggested aneurysmal dilation of the right coronary artery and a possible aorta-left main trunk connection. However, detailed echocardiography at 12 days of illness revealed an abnormal bifurcation of the proximal right coronary artery and no real connection of the aorta-left main trunk, all of which indicated the presence of a single right coronary artery. These diagnoses were confirmed by selective coronary angiography, which was performed later. Considering the difficulties in diagnosing congenital coronary anomalies, which may increase the risk of future fatal events, knowing the disease entity of the congenital coronary arterial anomaly is important for the accurate evaluation of coronary arteries in patients with Kawasaki disease. To the best of our knowledge, this is the first case report of a patient with Kawasaki disease complicated by a single right coronary artery; however, following a search of the literature, we found a brief conference abstract written in Japanese relating to the same clinical condition.